The Constitutionality of Compulsory Attendance at Religious Exercises in Religious Institutions of Higher Education Which Are the Recipients of State and Federal Financial Assistance - Habecker, Eugene B. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
The legal problems with which a religious higher education institution must deal if it receives state and/or federal financial assistance and requires attendance at its religious exercises are discussed. Selected state and federal court cases are reviewed and analyzed, including the United States cases of Tilton v. Richardson (1971), Lemon v. Kurtzman (1971), Hunt v. McNair (1973), and Roemer v. Board of Public Works (1976). Discussion of the three-fold judicial test of "secular legislative purpose,""primary effect," and "excessive entanglement" set forth by these Supreme Court and other court cases is followed by suggestions of practical guidelines which religious higher educational institutions can use to ascertain whether their institutional policies with regard to either receipt of state and/or federal financial assistance or requirements for attendance at religious exercises need to be revised. These kinds of institutions are reminded that courts generally do not require cessation per se of compulsory religious activities. On the other hand, receipt of government funds could mean that institutional recipients could be forced to choose between receipt of government financial aid or an institutional policy supportive of compulsory attendance at religious activities. (Author/MSE)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrative Policy; Attendance; Church Related Colleges; Constitutional Law; Court Litigation; Federal Aid; Government School Relationship; Higher Education; Legal Problems; Religious Education; State Aid; Student Rights; Supreme Court; Reports, Descriptive